2019
DOI: 10.17061/phrp28231810
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to low readiness and capacity of culturally diverse participants to use the Australian national bowel screening kit

Abstract: Objectives: Bowel screening is an effective way to promote early detection of bowel cancer. Culturally and linguistically diverse (CALD) people face considerable barriers to screening. This qualitative study explored perceptions towards, and usability of, Australia's national bowel screening kit with members of two migrant communities. Methods: Thirty-three people (aged 50-79 years) from Serbian and Macedonian communities in the Illawarra region in New South Wales, Australia, participated in one of five intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Troublesome operation of stool specimen collection is considered one of the obstacles affecting participation in colorectal cancer screening [ 13 , 32 , 34 , 36 , 37 , 39 ]. In a typical fecal occult blood test, fecal immunochemical-based test, or other stool-based occult blood tests, stool specimen collection is difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Troublesome operation of stool specimen collection is considered one of the obstacles affecting participation in colorectal cancer screening [ 13 , 32 , 34 , 36 , 37 , 39 ]. In a typical fecal occult blood test, fecal immunochemical-based test, or other stool-based occult blood tests, stool specimen collection is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, current fecal occult blood tests generally require the user to collect fecal specimens using sticks to scoop stool after defecation. This unpleasant process could affect the widespread utilization of fecal occult blood tests for colorectal cancer screening [ 32 - 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The detection phase of the cancer care continuum was measured through screening services and reported in twenty-two studies [ 29 – 50 ]. Six studies reported on the barriers and/or facilitators to screening services for cervical, breast and colorectal cancer [ 30 32 , 39 41 ]. Common barriers identified were lack of screening knowledge, feelings of embarrassment, fear over the gender of health provider, privacy concerns, religious and cultural beliefs, language barriers, fatalistic views of cancer, screening not being promoted in community languages and location of services [ 30 32 , 39 , 40 ].…”
Section: Main Textmentioning
confidence: 99%
“…Troublesome operation of stool specimen collection is considered one of the obstacles affecting participation in colorectal cancer screening [13,32,34,36,37,39]. In a typical fecal occult blood test, fecal immunochemical-based test, or other stool-based occult blood tests, stool specimen collection is difficult.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Moreover, current fecal occult blood tests generally require the user to collect fecal specimens using sticks to scoop stool after defecation. This unpleasant process could affect the widespread utilization of fecal occult blood tests for colorectal cancer screening [32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%